Study of Substituent Effect on Properties of Platinum(II) Porphyrin Semiconductor Using Density Functional Theory - Harno Dwi Pranowo; Fadjar Mulya; Hafiz Aji Aziz; Grisani Ambar Santoso (Universitas Gadjah Mada, 2018)
Study of substituent effect on properties of platinum(II) porphyrin had been performed using DFT method. The aim of the study is to investigate the effect of substituent group on the electronic and optical properties of the platinum(II) porphyrin. Geometry optimization was conducted using DFT/B3LYP/LANL2DZ to obtain molecular structure, electronic structure and energy profile. Band gap energy (Eg), the density of states (DOS), and UV-visible spectra are the semiconductor parameters to study. Computational results show that platinum(II) porphyrin and substituted platinum(II) porphyrin have properties of semiconductor based on Eg value, DOS, and UV-visible spectra. The results show that Mulliken partial charges of electron withdrawing substituents are higher than the electron donating substituents (CH3, OH, and NH2). Eg values of the complexes with respect to the substituents follow this order: NH2 < OH < NO2 < COOH < I < CH3 < Br < F < H, for DOSHOMO values, the order is CH3 < NO2 < I < OH < F < NH2 < COOH < Br < H and the maximum wavelength (λmax) for UV-visible adsorption spectra follows this order: NH2 > OH > COOH > NO2 > I > Br > CH3 > F > H. Molecules with smaller Eg and DOSHOMO values and higher λmax are considered as the most appropriate semiconductor materials. Our results show that Pt(II)P-NH2 has the smallest Eg and the highest λmax among other substituted platinum(II) porphyrin molecules. Therefore, Pt(II)P-NH2 are the most suitable semiconductor material based on the aforementioned criteria.